2003
DOI: 10.1021/ja028806h
|View full text |Cite
|
Sign up to set email alerts
|

An Unnatural Hydrophobic Base Pair with Shape Complementarity between Pyrrole-2-carbaldehyde and 9-Methylimidazo[(4,5)-b]pyridine

Abstract: An unnatural hydrophobic base, pyrrole-2-carbaldehyde (denoted as Pa), was developed as a specific pairing partner of 9-methylimidazo[(4,5)-b]pyridine (Q). The Q base is known to pair with 2,4-difluorotoluene (F) as an isostere of the A-T pair, and F also pairs with A efficiently in replication. In contrast, the Q-Pa pair showed specific selectivity in replication, and the five-membered-ring base Pa paired efficiently with Q but paired poorly with A. In addition, the interaction of Pa with DNA polymerases was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 37 publications
0
78
0
4
Order By: Relevance
“…The latest research indicated when the adsorbate has similar structures with functional groups of resin selectively, adsorption would be formed based on hydrophobic interaction (20,33). The mother nucleus of all flavonoids mentioned were QCCR's functional group (Fig.…”
Section: Results and Discussion Selective Adsorption Of Flavonoids Onmentioning
confidence: 99%
“…The latest research indicated when the adsorbate has similar structures with functional groups of resin selectively, adsorption would be formed based on hydrophobic interaction (20,33). The mother nucleus of all flavonoids mentioned were QCCR's functional group (Fig.…”
Section: Results and Discussion Selective Adsorption Of Flavonoids Onmentioning
confidence: 99%
“…Die Verwendung nichtkanonischer Nucleotide zur Bildung eines neuen Watson-Crick-Basenpaars wird bereits ausführlich diskutiert. [205][206][207] Um die Probleme zu umgehen, die mit der Konkurrenz durch Freisetzungsfaktoren in suppressionsbasierten Methoden einhergehen, erforschten Kowal und Oliver [173] …”
Section: Weitere Ansätzeunclassified
“…Ein solches neues DNA-Basenpaar würde den Informationsgehalt der DNA vergrößern, indem es das genetische Alphabet um ein drittes Basenpaar bereichert. [205,206,222] …”
Section: Dna-nucleotid-analogaunclassified
“…However, both dF and dZ also elicit natural bases, and so are not suitably orthogonal. Improvements by the Kool and Yokoyama groups have led to the development of pyrrole-2-carbaldehyde (dPa) and 9-methylimidazo[(4,5)-b]pyridine (dQ), which forms a stable base pair in DNA that is effectively replicated and extended, although dPa is still compromised by spurious insertion of dA [97]. These bases are essentially shape-complementary to the natural purine:pyrimidine pairs, and they all possessed minor-groove hydrogen-bonding functionalities.…”
Section: Recoding -Beyond Amber Suppressionmentioning
confidence: 99%